CXCL12‐mediated feedback from granule neurons regulates generation and positioning of new neurons in the dentate gyrus. Issue 8 (14th March 2018) - Abe, Philipp; Wüst, Hannah M.; Arnold, Sebastian J.; van de Pavert, Serge A.; Stumm, Ralf
Abstract: Adult hippocampal neurogenesis is implicated in learning and memory processing. It is tightly controlled at several levels including progenitor proliferation as well as migration, differentiation and integration of new neurons. Hippocampal progenitors and immature neurons reside in the subgranular zone (SGZ) and are equipped with the CXCL12‐receptor CXCR4 which contributes to defining the SGZ as neurogenic niche. The atypical CXCL12‐receptor CXCR7 functions primarily by sequestering extracellular CXCL12 but whether CXCR7 is involved in adult neurogenesis has not been assessed. We report that granule neurons (GN) upregulate CXCL12 and CXCR7 during dentate gyrus maturation in the second postnatal week. To test whether GN‐derived CXCL12 regulates neurogenesis and if neuronal CXCR7 receptors influence this process, we conditionally deleted Cxcl12 and Cxcr7 from the granule cell layer. Cxcl12 deletion resulted in lower numbers, increased dispersion and abnormal dendritic growth of immature GN and reduced neurogenesis. Cxcr7 ablation caused an increase in progenitor proliferation and progenitor numbers and reduced dispersion of immature GN. Thus, we provide a new mechanism where CXCL12‐signals from GN prevent dispersion and support maturation of newborn GN. CXCR7 receptors of GN modulate the CXCL12‐mediated feedback from GN to the neurogenic niche. Main Points: Mature dentate gyrus granule neurons express CXCL12 and CXCR7. Neuron‐derived CXCL12 restricts cell dispersion, regulates differentiation and promotes integration of new neurons. Neuronal CXCR7 influences progenitor behavior and cell dispersion.